2016
DOI: 10.1371/journal.pone.0164243
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of the Heterodimer Formation between Cell Shape-Determining Proteins Csd1 and Csd2 from Helicobacter pylori

Abstract: Colonization of the human gastric mucosa by Helicobacter pylori requires its high motility, which depends on the helical cell shape. In H. pylori, several genes (csd1, csd2, csd3/hdpA, ccmA, csd4, csd5, and csd6) play key roles in determining the cell shape by alteration of cross-linking or by trimming of peptidoglycan stem peptides. H. pylori Csd1, Csd2, and Csd3/HdpA are M23B metallopeptidase family members and may act as d,d-endopeptidases to cleave the d-Ala4-mDAP3 peptide bond of cross-linked dimer murope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 62 publications
3
20
0
Order By: Relevance
“…5A and C). The Csd1/Csd2 results further support published structural findings by An et al, who reported that Csd2 exists as both a monomer and dimer and that Csd1 and Csd2 form a heterodimer (17). An interaction signal was not detected between Csd7 and CcmA by BACTH ( Fig.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…5A and C). The Csd1/Csd2 results further support published structural findings by An et al, who reported that Csd2 exists as both a monomer and dimer and that Csd1 and Csd2 form a heterodimer (17). An interaction signal was not detected between Csd7 and CcmA by BACTH ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…Wild-type (no tag) and RecA-FLAG extracts were used as negative controls (see Table S5). In accordance with published findings and our interaction data, mass spectrometry identified both Csd1 and Csd2 as top hits for both the Csd1-FLAG and Csd2-FLAG IP samples (Table 3; see Table S6 to S8) (17). For Csd7-FLAG, Csd1, Csd2, and CcmA were among the top scoring protein hits (Table 3).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations